Evaluation of the atrial fibrillation better care pathway in the ENGAGE AF-TIMI 48 trial. Issue 11 (26th August 2022) - Patel, Siddharth M; Palazzolo, Michael G; Murphy, Sabina A; Antman, Elliot M; Braunwald, Eugene; Lanz, Hans-Joachim; Lip, Gregory Y H; Giugliano, Robert P; Ruff, Christian T
Abstract: Aims: The Atrial fibrillation Better Care (ABC) pathway is endorsed by guidelines to improve care of patients with atrial fibrillation (AF). However, whether the benefit of ABC pathway-concordant care is consistent across anticoagulants remains unclear. We assessed the association between ABC-concordant care and outcomes in this post hoc analysis from the ENGAGE AF-TIMI 48 trial, which was reported prior to the initial description of the ABC pathway. Methods and results: Patients were retrospectively classified as receiving ABC-concordant care based on optimal anticoagulation, adequate rate control, management of co-morbidities and lifestyle measures. Associations between ABC-concordance and outcomes were assessed with adjustment for components of the CHA2 DS2 -VASc and HAS-BLED scores. Of 20 926 patients, 7915 (37.8%) satisfied criteria of ABC-concordant care, which was associated with significantly lower incidence of stroke or systemic embolic event [stroke/SEE: hazard ratio (HRadj ): 0.54; 95% confidence interval (CI): 0.47–0.63], major bleeding (HRadj 0.66; 95% CI: 0.58–0.75), major adverse cardiac events (HRadj 0.53; 95% CI: 0.48–0.58), primary net clinical outcome (composite of stroke/SEE, major bleeding or death; HRadj 0.61; 95% CI: 0.56–0.65), cardiovascular (CV) hospitalization (HRadj 0.78; 95% CI: 0.74–0.83), CV death (HRadj 0.52; 95% CI: 0.46–0.58), and all-cause mortality (HRadj 0.56; 95% CI: 0.51–0.62), P < 0.001 for each. These associations were qualitatively consistent for both edoxaban and warfarin and across patient subgroups. Conclusion: Atrial fibrillation Better Care pathway-concordant care is associated with reductions across multiple CV endpoints and all-cause mortality, with benefit in edoxaban- and warfarin-treated patients and across patient subgroups. Increasing implementation of ABC-concordant care may improve clinical outcomes of patients with AF irrespective of anticoagulant. Graphical Abstract: Graphical Abstract In the ENGAGE AF-TIMI 48 trial, patients receiving care according to the Atrial fibrillation Better Care (ABC) pathway had lower adjusted risk for all clinical endpoints, with benefit irrespective of randomized anticoagulation to warfarin or edoxaban.